2020
DOI: 10.7150/ijbs.48991
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Insight into the asymptomatic SARS-COV-2 infection and transmission

Abstract: The existence of a substantial but unclear number of asymptomatic SARS-COV-2 patients worldwide has raised concerns among global public health authorities. In this review, according to the published literature, we provided the evidence that asymptomatic infections can result in person-to-person transmission. Four studies suggested that the virus can be transmitted by asymptomatic patients for at least two consecutive generations, indicating its strong infectivity. Asymptomatic infection tends to be, but is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 75 publications
0
70
0
1
Order By: Relevance
“…We include the asymptomatic carriers of the SARS-CoV-2, who are nevertheless able to spread the virus. The reason to include them is that asymptomatic people are very important contributors in the spread of the SARS-CoV-2, and this subpopulation has been considered in other studies related to the COVID-19 pandemic [20,72,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. It has been found that quantitative SARS-CoV-2 viral loads were similarly high for infected individuals with symptoms, pre-symptomatic, or asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…We include the asymptomatic carriers of the SARS-CoV-2, who are nevertheless able to spread the virus. The reason to include them is that asymptomatic people are very important contributors in the spread of the SARS-CoV-2, and this subpopulation has been considered in other studies related to the COVID-19 pandemic [20,72,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. It has been found that quantitative SARS-CoV-2 viral loads were similarly high for infected individuals with symptoms, pre-symptomatic, or asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the infected reported cases have uncertainties due to many factors such sensitivity and specificity of COVID-19 tests [10, 127]. Moreover, asymptomatic cases represent a great uncertainty [31, 43, 52, 62, 90, 100, 124, 132, 7]. Taking into account these uncertainties, we set the initial conditions presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…We use this value based on information from the CDC official website, even though it is mentioned that there is uncertainty in this percentage. We found that there is a large uncertainty in scientific literature regarding this percentage [30, 31, 43, 52, 62, 90, 100, 124, 132, 7]. Therefore, we vary it in order to deal with its uncertainty.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the virus has potentially unfavorable outcomes for both mother and fetus during the perinatal period (18). Although reports have suggested a lower prevalence in pediatric populations (19)(20)(21), Castagnoli et al (5), in their systematic review of 18 studies, identified 1,065 pediatric cases of SARS-CoV-2 infection. Clinical manifestations of the disease in children might be less severe as compared with adult patients (6,7,(21)(22)(23)(24)(25), however, younger children and infants are more susceptible to infections (24).…”
Section: Introductionmentioning
confidence: 99%